Formation of misfit dislocation arrays and helium nanochannels near copper surface assisted by high-temperature graphene deposition. (15th September 2022) - Yang, K.M.; Liu, G.S.; Ma, H.Y.; Song, J.; Li, Q.; Chen, N.Q.; Wang, Y.Q.; Chen, D.; Liu, Y.; Fan, T.X.
Abstract: Misfit dislocation arrays (MDAs) at semi-coherent heterogeneous interface have been demonstrated effectiveness to trap and then outgas helium (He) for alleviating void swelling in metals, but limited by atomic-level thin film deposition that is difficult to scale-up for industrial production. In this work, we proposed an innovative strategy that could generate semi-coherent homophase interfaces in a same grain by varying surface energy density assisted by high-temperature graphene (Gr) deposition. This strategy transforms strain energy and surface energy, two originally distinctive processes into successive processes, and demonstrates experimentally and theoretically by introducing 111 copper (Cu) in a 100 Cu grain. Subsequent He implantation and electrical resistivity measurement results suggest that high-density MDAs originated at this 111/100 interface could form stable He nanochannels near Cu surface with Gr assistance, manifesting by ultra-low increased ratio of the electrical resistivity (i.e. ∼3800% of Cu vs. ∼90% of Gr/Cu) after He implantation. The present findings may provide a new strategy for efficiently managing He and achieving surface protection of advanced metals, merely by depositing a super-rigid material on metal surface to greatly reduce surface energy density. Graphical abstract: Image, graphical abstract